ANALYSIS OF THE BEHAVIOR OF BIOTIC VARIABLES IN THE LACHAY NATIONAL RESERVE DURING THE EL NIÑO EVENT (1998-2001, 2010) - Castañeda Córdova, Liz Zaida (2022)
This study is based on the studies of herbaceous plants, birds and coleoptera that were carried out between 1998 and 2001 in the Lachay National Reserve, and is based on the interest of generating a biological early warning of the El Niño event. The present study incorporated two samples for beetles in 2002 and two samples for each group in 2010. The objective of the research was to evaluate the variation of the biotic variables of the three biological groups under the El Niño Event between 1998-2001 and 2010, to identify indicator variables of the El Niño Event. In the plots, composition, abundance, diversity, and functional groups were estimated. In addition, for herbaceous plants, vegetation cover, density, IVI and Cinv were evaluated. Some variables (Cinv Abundance, Cinv Coverage, Cinv IVI native and/or endemic and in vegetation coverage) suggest a positive relationship with the Global Niño because they increase after its manifestation, from a very strong to moderate El Niño event, favoring the appearance of endemic herbaceous species. Other variables proposed for monitoring are the abundance and richness of beetles, alpha diversity and richness of birds, as well as the percentage of abundance of chamaephytes, the percentage of abundance of nanophanerophytes, and the abundance of predatory group. Some key species are Croton ruizianus, Trixis cacalioides, Crassula connata, Fuertesimalva peruviana, Nicotiana paniculata, and IVIg as key variable.